Selfhood and Promise. The person as a mutual co-creation from the notion of narrative identity of Paul Ricoeur - Quiceno, Juan David (Pensamiento. Revista de Investigación e Información Filosófica, 2023)
The article analyzes the relationship between selfhood and promise according to the perspective of the narrative identity proposed by Paul Ricoeur. From this perspective, the promise appears as a paradigm of the selfhood, because, in it, identity appears as a pole of responsibility, creativity and intersubjectivity. The article ends with the attempt to outline the ontology behind the narrative identity thesis.
Keywords: narrative identity; selfhood; promise; creative innovation; Capacity and responsibility; intersubjectivity